The attitude of the Soviet authorities towards the material and cultural monuments of Uzbekistan (1917–1990) (International conference on multidisciplinary science, 2025)
The article analyzes the policies and practical measures taken in relation to monuments of material and cultural heritage in Uzbekistan during the Soviet period. In particular, attention will be paid to the destruction of religious monuments and historical architectural monuments, the change in their function, as well as the ideological purposes that the surviving parts of them served. The study is based on historical sources, archival documents and modern analysis.